SAT0245 Evaluation of Lesions in the Zygapophyseal Joints and their Correlation with Functional Changes in Patients with Ankylosing Spondylitis. (23rd January 2014) - Kovalenko, S.; Protsenko, G.; Kachur, V.; Kateryna, I.
Abstract : Background: Ankylosing spondyloarthritis (AS) is a chronic inflammatory rheumatic disease. Lesion of zygapophysial joints is characterized by more unfavorable course of disease. Objectives: To estimate the lesion frequency of the zygapophysial joints by MRI and its impact on vertebral function in patients with AS. Methods: The study involved 53 people (males) with AS and disease duration ≤ 10 years. The patients were divided into two groups: Group I – patients without lesion of zygapophysial joint but have syndesmophytis (18 people), Group II – patients with lesion of zygapophysial joint (35 people). All evaluation parameters: 10-point assessment of mobility of the spine in the cervical, thoracic, lumbar parts. Results: Zygapophysial joint lesion has a high prevalence at onset disease (61, 40%) and precedes, in most cases, by lesions of the vertebral body and ligaments. Involvement of that kind met mostly in patients with peripheral form of the disease: 25 patients (71.42%), especially if the peripheral joints were affected at onset disease. Spinal mobility's indicants in patients without zygapophysial joint lesions but with the presence of syndesmophyte: neck rotation 1.94 ± 0.70 points, chest excursion 4.32 ± 0.57 cm, lateral flexion 2.88 ± 0.85 points, modified Schober test 5.33 ± 0.83 points. Spinal mobility's indicants in patients with zygapophysial joint lesions: neck rotation 4.57 ± 0.38 points, chest excursion 2.79 ± 0.27 cm, lateral flexion 5.22 ± 0.41 points, modified Schober test 7.87 ± 0.35 points. We also notified the correlation between the quantity of affected joints and intensity of functional changes in spine mobility. Conclusions: We observed the correlation between severity of function changes in the cervical and lumbar spine, chest excursion and the presence of facets joints lesions. The differences between groups with and without facet joint lesions were statisticaly significant, that indicates more unfavourable prognosis for a clinical course. Disclosure of Interest: None Declared